The Role of Transformational Leaders in Improving the Quality of Early Childhood Education - Widyastuti, Niken; Suminar, Tri; Waluyo, Edi (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
This research examines the application of transformational leadership principles by the Satria Tunas Bangsa PAUD principal and its impact on learning. The research focus includes the implementation of transformational leadership, leadership learning strategies, supporting factors, and the impact of this leadership. The research results show that school principals play an important role in creating a positive learning environment by displaying leadership charisma, providing inspirational motivation to teachers, and paying attention to individual needs. In the learning leadership strategy, the principal develops a clear vision, creates a conducive learning environment, and supervises and provides professional support. Supporting factors include a positive organizational culture, a conducive climate, stakeholder support, and the principal's leadership competence. The impact of transformational leadership can be seen in improving the quality of learning, teacher motivation and performance, developing student character, as well as increasing innovation and creativity in learning. This research concludes that transformational leadership in PAUD Satria Tunas Bangsa makes a significant contribution to improving the quality of education and student achievement.